Diseño Operacional de las rutas y frecuencias del sistema de transporte masivo Intracantonal, de la troncal Ferroviaria (terminal terrestre) Machala – Pto Bolívar, de la Ciudad de Machala, año 2015 - Alarcón Benavides, Dionicio Honorato (2015)
The lines of urban mass transportation of passengers from the city of Machala are inefficient, affecting mobility and travel times of users to their respective points of arrival and therefore socio-economic development of its inhabitants; For this reason, the present work aims Titling the layout and design of a new route and frequencies that meet design standards, helping its future implementation. The research was used descriptive statistics methodology, gauging traffic volumes, TPDA, capacity and service level of road circuit, household surveys and bus passenger counting the route were made. The results of vehicle capacity, household surveys, passenger counting, internet consultation and field research, environmental impact, were considered for the layout and design of the route; with a volume of 84976 users psj. / Day, a TPDA of 52192, an average speed of operation or 24 km / h, 715 travel intentions, road capacity of 2337-6577 veh. / H, service levels pathways ranging from A to F, 78 urban bus stops, 3672 frequencies and poor signage